PAG-IBIG ; Chirstmas [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
The fund that provides opportunities for people to own their lots meets with success when a squatter colony pulls its resources own a piece of property. A look at Christmas homes, i.e., Gigi Carlos who decorated her home for six month.